Investigating the Factors Affecting Internet Sex Addiction - Sheibani-Noqabi, Mehrnaz; Arjomand, Mohamad Tolooe (New Visions in Medicine and Medical Science Vol. 9, 2024)
Today, with the advancement of technology and the use of the internet on smartphones, private interactions of individuals with strangers in the virtual space take a harmful form regardless of location. Problematic use of the Internet is now a concerning area across the globe, referring to excessive engagement in online activities known to be associated with marked functional impairment. A significant portion of people's communications takes place on social networks and through cyber facilities. The debate on human dependence on technology and cyber facilities has reached a point where the use of these facilities has become an inseparable part of many people's lives, work, and relationships. The increasing use of cyber facilities and individuals' membership in online social networks and chat rooms, alongside easy access to relationships with strangers, sometimes leads to the emergence of cybersex relationships and conversations aimed at satisfying instinctual and sexual desires. In this chapter, after defining internet sex addiction, sexual identity, and Body Dysmorphic Disorder (BDD), the relationship between internet sex addiction and Body Dysmorphic Disorder (BDD) in men is examined. The impact of these items on each other and diagnostic and treatment methods are explained. The present research is correlation-relation research in which inferential statistics were used. Sexual Addiction Screening-Test-Revised (SAST-R) was used as a research tool in which 45 yes or no questions were included. The test has a main part and two subscale groups. The results of this research show that the body dysmorphic disorder variable has a correlation of 66.6%, and 44.3% predicts the level of internet sex addiction. Finally, it is concluded that there is an indirect and significant correlation between Internet sex addiction and body image.